(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Recently, it was shown that Shigella, a Gram-negative bacterium that causes gastrointestinal illnesses, has complex interactions with host cells that affect the biology of cancer. Through immunological dysregulation, DNA damage, and inflammation, Shigella infections can accelerate the development of tumors. Shigella also has effector proteins that can cause apoptosis, which could lead to specific anti-cancer treatments. Objective: The objective of this narrative review is to understand the Double-Edged Sword of Shigella in Oncology: From Tumorigenic Inflammation to Apoptotic Therapy. Methodology: The present literature on Shigella’s dual role in cancer biology and therapy was methodically examined in order to undertake this review. Studies that focused on Shigella’s interactions with host cells, its function in the formation of cancer and chronic inflammation, and its potential use in anti-cancer therapy were considered relevant. Information about apoptotic processes, effector proteins (IpaB, IpaC, and Osp), Shigella-induced molecular pathways, and developments in genetically engineered strains for targeted therapy were retrieved. It’s a narrative pre review that abstract from online PubMed, Google scholar and Database. Conclusion: Shigella plays a dual role in cancer, potentially promoting carcinogenesis by persistent inflammation and serving as a prospective anti-cancer therapeutic agent through immune regulation and apoptosis. Shigella strains that have undergone genetic engineering have prospects for tailored tumor therapy, underscoring its potential in precision oncology. Developing safe and efficient bacterial-based cancer therapeutics requires an understanding of this "double-edged sword" nature.